Contextualizing Research Tools & Services Through Workflows in the SSH Open Marketplace - Laure Barbot; Maja Dolinar; Edward J. Gray; Cristina Grisot; Klaus Illmayer; Michael Kurzmeier; Barbara McGillivray (Journal of Open Humanities Data)
This paper provides an overview of workflows in the Social Sciences and Humanities Open Marketplace discovery portal. Workflows are defined as step-by-step research scenarios pointing to resources that can be used at each stage for someone to reproduce these scenarios. Born as TEI objects in the Standardization Survival Kit, a mapping exercise was needed to transfer them into the SSH Open Marketplace and ensure their legacy. Dedicated forms are now available to create and edit workflows which provide an easy to use interface for researchers to be autonomous in the creation and design of their workflows. This paper reviews the history, the technical, and community dimensions needed to describe research workflows in the Social Sciences and Humanities. It also describes the challenges faced and the new developments envisioned so that these workflows can better reflect and serve SSH researchers.